Corruption consolidation in local governments: A grounded analytical framework. (12th October 2020) - Meza, Oliver; Pérez‐Chiqués, Elizabeth
Abstract: This article constructs a grounded framework to study how corruption is consolidated in local governments. We focus on the fine‐grained texture of corrupt practices that can only be achieved by looking at rich contextual studies. We argue that neglecting the way corruption becomes the 'rule of the game' has led to the creation of anti‐corruption policies that tend to be overly reliant on formal institutions, addressing only dyadic and venal types of corruption, and have therefore proven ineffective. Based on a two‐staged, mixed methods research design—including 50 in‐depth interviews in two Mexican cities and three surveys applied to citizens and public officials—this article's framework focuses on how networks are shaped and organized to perform corrupt practices, and how opacity and weak checks and balances grant them impunity. Results show corrupt schemes to be outstandingly malleable and resilient, able to circumvent formal anti‐corruption strategies.